MACHADO, Eliel; GASPAR, Ronaldo (Orgs.). - REA, Editor (Revista Espaço Acadêmico, 2021)
MACHAD0, Eliel; GASPAR, Ronaldo (Orgs.). 100 anos da Revolução de Outubro (1917-2017): balanços e perspectivas. Londrina: EDUEL, 2020 (322 p.).